1989
DOI: 10.1007/bf02385411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of martensite strength on the tensile strength of dual phase steels

Abstract: Fe-2% Si-1.5% Mn steels with three levels of carbon content (0.10, 0.14 and 0.19wt%) were intercritically annealed followed by water quenching to obtain dual phase (martensite plus ferrite) structure. It is found that the ultimate tensile strength of dual phase steels increased with increasing the volume fraction as well as the tensile strength of martensite. The tensile strength of dual phase steel can be predicted using the law of mixtures although the predicted tensile strength is slightly higher than the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
4

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 7 publications
5
43
0
4
Order By: Relevance
“…This seems consistent with the design basis for these steels, since the volume fraction of martensite mainly determines the strength and hardness of DP steels. 2,23) As well, this result agrees with previous findings showing that the volume fraction of martensite in the DP steels determined the reduction of ultimate tensile strength when the HAZ was simulated in DP steels using a Gleeble thermal simulator. 15) …”
Section: Effects Of Martensite Content On Maximum Haz Softeningsupporting
confidence: 91%
“…This seems consistent with the design basis for these steels, since the volume fraction of martensite mainly determines the strength and hardness of DP steels. 2,23) As well, this result agrees with previous findings showing that the volume fraction of martensite in the DP steels determined the reduction of ultimate tensile strength when the HAZ was simulated in DP steels using a Gleeble thermal simulator. 15) …”
Section: Effects Of Martensite Content On Maximum Haz Softeningsupporting
confidence: 91%
“…Reduction in strength due to higher V m % and less carbon in martensite observed in present study is in agreement with the findings of other researchers [1,8,12,17]. …”
Section: Fig 7 Microstructure Of B3 Soaked For 3hrs At 800oc Consissupporting
confidence: 94%
“…The mechanical properties of DP steels are directly related to the synergistic effect of two phases present in these steels in which martensite controls the strength of the steel while ferrite is responsible for formability properties [7][8][9]. Numerous studies have reported that the mechanical properties of ferrite-martensite DP steels have been quite [1,3,5-6,8-10,12-13,] suggest that the mechanical behavior of ferrite-martensite DP microstructure cannot be predicted by the general rule of mixture law.…”
Section: Effect Of Intercritical Heat Treatment On Mechanical Propertmentioning
confidence: 99%
See 1 more Smart Citation
“…8 the constituent properties (strength, formability, etc.) [23][24][25][26][27][28][29][30] of the ferrite/martensite phases. In order to understand the deformation mechanisms of nano-precipitated DP steels, the effect of these factors on mechanical properties should systematically be investigated.…”
Section: Introductionmentioning
confidence: 99%